The Effectiveness of OsiriX and the Anatomage Virtual Dissection Table in Enhancing Neuroanatomy and Neuroradiology Teaching - Sadiq, Zuhair; Laswi, Ibrahim; Raoof, Ameed (Advances in medical education and practice, 2023)
Introduction: In recent years with the advent of technology in medical education, teaching methodology has shifted towards heavy use of online-learning modalities. This has been especially the case for anatomy and radiology courses since they require students to visualize structures of the human body. Several studies indicated that Anatomage and OsiriX can be effective at enhancing students' learning experiences in anatomy and radiology. Purpose: This aim of this study is to assess the effectiveness of online case- based learning modules in teaching medical students about the anatomy and radiology of different types of brain tumors. Methods: Two online case-based learning modules were designed using Anatomage Table[R] and OsiriX DICOM viewer[R], consisting of a clinical case and CT and MRI images. We recruited 36 fourth-year medical students that completed two 10-question quizzes (one on glioblastoma multiforme and one on pituitary adenomas). Participants were randomly assigned to either a study group that completed both modules prior to completing the quizzes, or a control group that completed the quizzes without access to the modules. The performance of both groups was compared to assess the effectiveness of the modules. Participants in the study group also completed a feedback survey to assess the quality and convenience of using the modules. Results: Students who used the case-based learning modules performed significantly better than those who did not (Quiz 1: mean = 6.56 vs 3.28, p<0.01. Quiz 2: mean = 6.67 vs 3.06, p<0.01). Students who completed the modules would like to see similar modules used in teaching anatomy and radiology in the future (64%). They found them easy to navigate (72%), useful in teaching anatomy and radiology (72%), and helpful in improving understanding of anatomical and radiological clinical correlations (77%). Conclusion: Online case-based learning modules created using Anatomage and OsiriX can be used effectively in teaching medical students about the anatomy and radiology of different types of brain tumors. Keywords: anatomage, OsiriX, neuroanatomy, radiology, brain tumors, medical education